Prevalence of Triticeous Cartilage: A Descriptive Cross-Sectional Study - Pandit, Ruku; Yadav, Pranav Kumar; Manjappa T; Sharma, Nitasha (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Triticeous cartilage is a small cartilage resembling a wheat grain, embedded in the lateral thyrohyoid ligament. It is believed to support thyrohyoid ligaments by adding strength to it. The aim of the study is to ﬁnd out the prevalence of triticeous cartilage in cadavers. MATERIAL AND METHODS The study was carried out in the Department of Anatomy of College of Medical Sciences from February to October 2021 after taking an ethical approval from the Institutional Review Committee (Ref. No. COMSTH-IRC/2021-58). Thirty laryngeal preparations from formalin embalbed cadavers of both sexes were obtained. Presence or absence of triticeous cartilage was noted in the lateral thyrohyoid ligament. RESULTS In the present study, triticeous cartilage was observed in 30% of cadavers. The occurrence of triticeous cartilage in male was 23.33% and that in female was 6.67%. Of nine cadavers with triticeous cartilage, three (10%) had unilateral triticeous cartilage while six (20%) had bilateral triticeous cartilage. Among unilateral triticeous cartilage, all three were present on the left side. CONCLUSION The prevalence of triticeous cartilage is quite variable. The clinician must consider the existence of triticeous cartilage while making differential diagnosis of neck pathologies like the calciﬁc deposits in the soft tissue of neck, carotid atheroma and fracture of superior cornu of thyroid cartilage.